An Agent-based Simulation of a QoS-oriented Supply Chain - Gumzej, Roman; Rosi, Bojan (Promet - Traffic&Transportation, 2017)
With adaptive customer-orientation the efficiency of supply chain management is improved substantially. By the introduction of service quality-based decision-making into supply chain management the quality of service (QoS) within supply chains is expected to improve autonomously and continuously up- and downstream. In the paper the main characteristics of quality of service oriented supply chain management are outlined. The quality of service criterion, introduced into the adaptive supply chain model, provides market regulators and managements with the needed information and feedback to their increasingly informed decisions. By an experiment comprising several typical scenarios on our agent-based simulation model it was possible to empirically verify the expected impact of quality of service- based reasoning on generic adaptive supply chains.